In vitro and in silico evaluation of synthetic compounds derived from bi-triazoles against asexual and sexual forms of Plasmodium falciparum - Leandro do Nascimento Martinez; Minelly Azevedo da Silva; Saara Neri Fialho; Marcinete Latorre Almeida; Amália dos Santos Ferreira; Aurileya de Jesus Gouveia; Welington da Silva Paula do Nascimento; Ana Paula de Azevedo dos Santos; Norton Rubens Diunior Lucas Pejara Rossi; Jansen Fernandes de Medeiros; Natalie Ferreira Araújo; Quelli Larissa Oliveira de Santana; et al. (Malaria Journal)
Abstract Background Despite advances in malaria chemotherapy, the disease continues to claim thousands of lives annually. Addressing this issue requires the discovery of new compounds to counteract resistance threatening the current therapeutic arsenal. In this context, bi-triazoles are substances with diverse biological activities, showing promise as lead compound to fight malaria. Triazoles are heterocyclic structures composed of five members, including three nitrogen atoms and two double bonds. Bi-triazoles, the focus of this study, are derivatives of triazoles consisting of two triazole rings (nitrogen heterocyclic) with isolated nuclei lacking a spacer and two substituents at each end. The goal of the present study was to assess the in vitro and in silico, antimalarial activity of bi-triazole compounds 14c, 14d, 13c, and 13d against asexual and sexual forms of Plasmodium falciparum. Methods For in silico predictions, the software OSIRIS, Molinspiration, and ADMETlab were employed. To determine the 50% inhibitory concentration (IC50) on the asexual forms, the W2 clone was used, while the strain NF54 was used to assess inhibition of sexual forms. Cytotoxicity was evaluated using the HepG2 cell line, and haemolysis tests were conducted. Additionally, the selectivity index (SI) of each compound was calculated. Results In silico analyses of physicochemical properties revealed that all compounds have favorable potential for drug development. Pharmacokinetics predictions also provided important, novel insights into this chemical class. Antimalarial activity tests showed that compounds 14d and 13d exhibited promising activity, with IC50 values of 3.1 and 4.4 µM, respectively. Antimalarial activity of compounds 14d and 13d may be related to the presence of methyl acetate in substituent R2 conjugated to the bi-triazole. None of the compounds demonstrated cytotoxic or haemolytic activity, with SI values above 51 for the three most active compounds, highlighting their selectivity. For the sexual forms, compounds 14c and 14d were classified as having a high potential to block malaria transmission. Conclusion Overall, the in vitro and in silico results showed that bi-triazole compounds may guide new biological investigation for malaria, enabling the identification and development of more active and selective antimalarial agents.